The Changing Legal Status of Cats in Australia: From Friend of the Settlers, to Enemy of the Rabbit, and Now a Threat to Biodiversity and Biosecurity Risk - Riley, Sophie (Frontiers in Veterinary Science, 2019)
In NSW, free-roaming cats are regarded as one the biggest threats to biodiversity. Yet, at one stage they were classified as “the enemy of the rabbit” and were protected and released in their thousands. The purpose of this article is to examine the changing status of cats in Australia, demonstrating that regulation frequently depends on a narrow set of values based on the usefulness of cats at a given point in time. By the late twentieth century, the status of free-roaming cats had changed from enemy of the rabbit, to threat to biodiversity and then in the twenty-first century, to a risk to biosecurity. Once the status of cats changed from enemy of the rabbit, management practices followed historically-driven pathways that rely on lethal methods, which do not necessarily prioritize efficacy, animal wellbeing, or changing community outlooks. This is reflected in current practice, which gives scant regard to non-lethal processes, such as Trap-Neuter-Release, and in some cases makes the feeding and release of free-roaming cats, illegal. This article argues that regulatory preferences for employing lethal methods, now occur in a society which increasingly questions the efficacy of these measures, as well as the very need to kill. While TNR is unlikely to provide a complete solution to the problem of free-roaming cats in Australia, given the success of TNR among community groups, accompanied by changing societal perspectives, the time has come for regulators to engage with alternative control methods and include them in their suite of official measures.